Integrating health and agriculture to maximize the nutritional impact of orange-fleshed sweetpotato: The Mama SASHA proof-of-concept project in Western Kenya - International Potato Center (2012)
High rates of participation from pregnant women during the full implementation suggest that the integration of orange-fleshed sweetpotato (OFSP), nutrition education and vine distribution into antenatal care is feasible and acceptable for health care providers, community health workers and pregnant women.